Proteome Analysis of Outer Membrane Vesicles From a Highly Virulent Strain of Haemophilus parasuis - Zhang, Kunli; Chu, Pinpin; Song, Shuai; Yang, Dongxia; Bian, Zhibiao; Li, Yan; Gou, Hongchao; Jiang, Zhiyong; Cai, Rujian; Li, Chunling (Frontiers in Veterinary Science, 2021)
Haemophilus parasuis (H. parasuis) has emerged as an important bacterial pathogen in pig husbandry. Since H. parasuis can co-infect pigs with a variety of pathogenic microorganisms and further cause an aggravation of the disease. It is crucial to investigate its pathogenetic mechanism. Outer membrane vesicles (OMVs) are naturally secreted by Gram-negative bacteria, their potent virulence factors play prominent roles which affect the interaction between bacteria and host, but the pathogenesis that associated with the bacterial OMVs has not been well elucidated. In this study, we investigated the secretion of OMVs from a clinical H. parasuis isolate strain (H45). In addition, we further analyzed the characterization, the comprehensive proteome and the virulence potential of OMVs. Our data demonstrated that H. parasuis could secrete OMVs into the extracellular milieu during infection. Using LC-MS/MS identification and bio-information analysis, we identified 588 different proteins associated with OMVs. And we also analyzed the subcellular location and biological function of those proteins. These proteins are mainly involved in immune and iron metabolism. Moreover, we confirmed the pathogenicity of H. parasuis OMVs through observing a strong inflammatory response in J774A.1 and PAMs. Taken together, our findings suggested that OMVs from H. parasuis were involved in pathogenesis of this bacterium during infection.